1984
DOI: 10.1037/0033-2909.96.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Predictable and unpredictable shock: Behavioral measures of aversion and physiological measures of stress.

Abstract: Previous articles have reviewed the behavioral literature and concluded that predictable shock conditions are less aversive than unpredictable shock conditions. This article reviews the literature on predictable and unpredictable shock conditions relative to physiological measures of stressfulness and considers the possible role of stress-induced analgesia in both the physiological and behavioral effects. It finds that unpredictable conditions are physiologically more stressful than predictable conditions when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 84 publications
8
77
0
1
Order By: Relevance
“…Using an operant paradigm, female and male rats were tested for drug SA with and without predictable or unpredictable acute and repeated stress. Consistent with earlier behavioral, immunological, and physiological reports (Abbott et al , 1984;Arthur, 1986;Glass & Singer, 1972;McKinnon et aI., 1989), predictability had a different effect on drug SA depending on whether the stressor was acute or chronic. Specifically, predictability of the stressor increased fentanyl SA with repeated exposure to the stressor, especially for female subjects.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Using an operant paradigm, female and male rats were tested for drug SA with and without predictable or unpredictable acute and repeated stress. Consistent with earlier behavioral, immunological, and physiological reports (Abbott et al , 1984;Arthur, 1986;Glass & Singer, 1972;McKinnon et aI., 1989), predictability had a different effect on drug SA depending on whether the stressor was acute or chronic. Specifically, predictability of the stressor increased fentanyl SA with repeated exposure to the stressor, especially for female subjects.…”
Section: Discussionsupporting
confidence: 87%
“…For example, Glass and Singer (1972) reported a series of human laboratory studies which found that predictability of a noise stressor attenuated the performance decrements that occurred after cessation of an acute unpredictable nois8 stressor . In contrast, under conditions of chronic stressor exposure, predictability potentiated behavioral , physiological, biochemical, and immunological stress responses (Abbott, Schoen, & Badia, 1984;Arthur, 1986;McKinnon, Weisse, Reynolds, Bowles, & Baum, 1989). This increase with repeated exposure to a stressor might reflect: (1) sensitization to the stressor; or (2) classical conditioning between the stimuli that predict the stressor and the stressor itself ( Pavlov, 1906;Rescorla, 1966;Rescorla, 1967).…”
Section: Predictability Of a Stressormentioning
confidence: 99%
See 2 more Smart Citations
“…Jay Weiss in the 1970s cleverly illustrated the importance of psychological factors, such as predictability and outlets for frustration, on the overall effect of a stressor 47 . When negative stimuli are predictable, animals know when to worry and when to relax [48][49][50] . Control, or the perception of control, over a stressor also has a big part on the physiological effect.…”
Section: Thermal Stress and Its Effect On Mouse Modelsmentioning
confidence: 99%